The Role of Religious and Secular Values in Youth Education (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article discusses the issues of educating the young generation in the spirit of religious, secular and national values in the process of deep social reforms, which are one of the most important features of our country today.